Association between resting-state brain functional connectivity and cortisol levels in unmedicated major depressive disorder. (October 2018) - Wang, Ying; Chen, Guanmao; Zhong, Shuming; Jia, Yanbin; Xia, Liu; Lai, Shunkai; Zhao, Lianping; Huang, Li; Liu, Tiebang
Abstract: Disturbed hypothalamus–pituitary–adrenal axis function, which leads to excessive and prolonged hypercortisolemia, is a core feature of major depressive disorder (MDD). However, the relationships between depression, brain structure and function, and cortisol levels are unclear. The current study examined the whole-brain functional connectivity pattern of patients with MDD and evaluated the association between functional connectivity and serum cortisol levels in MDD. A total of 93 unmedicated patients with MDD and 139 healthy control subjects underwent resting-state functional magnetic resonance imaging. Voxel-wise whole-brain connectivity was analyzed by using a graph theory approach: functional connectivity strength (FCS). A seed-based resting-state functional connectivity analysis was further performed to investigate abnormal functional connectivity patterns of those regions with changed FCS. Morning blood samples were drawn for cortisol measurements in some subjects (including 53 MDD patients and 30 controls). The MDD patients had a significantly lower FCS in the left posterior lobes of the cerebellum (mainly lobule Crus II) ( p  < 0.05, TFCE corrected). The seed-based functional connectivity analysis revealed decreased functional connectivity between the left posterior cerebellum and the left medial orbitofrontal cortex (OFC) ( p  < 0.05, TFCE corrected). Moreover, the functional connectivity between the left posterior cerebellum and the left medial OFC were significantly positively correlated with the serum cortisol levels in MDD patients. Our results suggest that cerebellar dysconnectivity, in particular distributed cerebellar–OFC functional connectivity, may be associated with serum cortisol levels in MDD patients.